2013
DOI: 10.1021/op400242j
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Synthesis of a Pyrrolotriazine–Fluoroindole Intermediate to Brivanib Alaninate: Process Development Directed toward Impurity Control

Abstract: The development of a practical, commercial process for the preparation of 4-fluoro-2-methyl-indol-5-ol and its subsequent coupling with a pyrrolotriazine to form an advanced intermediate of the oncology therapy brivanib alaninate is described. A key aspect is the multikilogram-scale preparation of the fluoroindole intermediate from trifluoronitrobenzene and the subsequent coupling while achieving impurity minimalization. As brivanib alaninate is a high-dose drug, the synthesis of high-quality API with low leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…The hydrolysis of 14 increased in the reaction with side product HCl autocatalyzing the reaction. Therefore, in the next attempt, we successfully applied the quenching and workup process by adopting the method developed by Pesti et al Cold aqueous K 2 HPO 4 would be an advantageous quench solution; as in the case of an accidental overcharge, it would not result in an overly caustic quench mixture. Moreover, using a base with more strength to neutralize acid, i.e., K 2 CO 3 , that required less water to dissolve per base equivalent, was not advantageous in the initial neutralization of POCl 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrolysis of 14 increased in the reaction with side product HCl autocatalyzing the reaction. Therefore, in the next attempt, we successfully applied the quenching and workup process by adopting the method developed by Pesti et al Cold aqueous K 2 HPO 4 would be an advantageous quench solution; as in the case of an accidental overcharge, it would not result in an overly caustic quench mixture. Moreover, using a base with more strength to neutralize acid, i.e., K 2 CO 3 , that required less water to dissolve per base equivalent, was not advantageous in the initial neutralization of POCl 3 .…”
Section: Resultsmentioning
confidence: 99%
“…For the large-scale synthesis quenching and workup of the reaction mixture to get the crude product 14 with high purity required careful handling, as the chlorinated product 14 at pH ≤ 3 or ≥ 10 hydrolyzed to the starting material 13. 22 Therefore, upon completion of the chlorination reaction, the batch temperature was decreased to 26 °C; this resulted in the solidification of the reaction mixture, which was difficult to handle. Moreover, when the reaction was diluted with DCM at the batch temperature of 26 °C, the brown sticky precipitate was suspended in the reaction mixture.…”
Section: Kilogram-scalementioning
confidence: 99%
“…This reagent is primarily used in the formylation of aromatics (VilsmeierHaack reaction (43)), as a phosphorylating agent, and a chlorination agent, particularly in the dehydroxychlorination of heteroaromatics (44). Due to a difference in reactivity, only one of the P-Cl bonds is utilized effectively in synthesis, with the result that the remaining two bonds must be hydrolyzed during the quench, (Figure 15).…”
Section: Phosphoryl Chloride (Pocl 3 )mentioning
confidence: 99%
“…We first present and describe the various sections of such a report and then illustrate its use by showing example reports for the industrial manufacture of three pharmaceuticals shown in Figure 1: 5-HT2B and 5-HT7 antagonist [25], brivanib [26][27][28][29], and orexin receptor agonist [30]. The pros and cons of each synthesis are discussed with respect to the three categories of green metrics mentioned above.…”
Section: Introductionmentioning
confidence: 99%